The EcoCyc Database in 2021 - Keseler, Ingrid M.; Gama-Castro, Socorro; Mackie, Amanda; Billington, Richard; Bonavides-Martínez, César; Caspi, Ron; Kothari, Anamika; Krummenacker, Markus; Midford, Peter E.; Muñiz-Rascado, Luis; Ong, Wai Kit; Paley, Suzanne; et al. (Frontiers in Microbiology, 2021)
The EcoCyc model-organism database collects and summarizes experimental data for Escherichia coli K-12. EcoCyc is regularly updated by manual curation of individual database entries such as genes, proteins and metabolic pathways and by programmatic addition of results from select high-throughput analyses. Updates to the Pathway Tools software that supports EcoCyc and to the web interface that enables user access have continuously improved its usability and expanded its functionality. This article highlights recent improvements to the curated data in the areas of metabolism, transport, DNA repair, and regulation of gene expression. New and revised data analysis and visualization tools include an interactive metabolic network explorer, a circular genome viewer, and various improvements to the speed and usability of existing tools.